Aerosol Properties Over the Indo‐Gangetic Plain: A Mesoscale Perspective from the TIGERZ Experiment - Giles, D. M.; Holben, B. N.; Tripathi, Sachchida N.; Eck, Thomas F.; Newcomb, W. Wayne; Slutsker, Ilya; Dickerson, Russell R.; Thompson, Anne M.; Mattoo, Shana; Wang, Sheng-Hsiang; Singh, Ramesh P.; Sinyuk, Aliaksandyr; et al. (Chapman University Digital Commons, 2011)
High aerosol loading over the northern Indian subcontinent can result in poor air quality leading to human health consequences and climate perturbations. The international 2008 TIGERZ experiment intensive operational period (IOP) was conducted in the Indo-Gangetic Plain (IGP) around the industrial city of Kanpur (26.51 degrees N, 80.23 degrees E), India, during the premonsoon (April-June). Aerosol Robotic Network (AERONET) Sun photometers performed frequent measurements of aerosol properties at temporary sites distributed within an area covering similar to 50 km(2) around Kanpur to characterize pollution and dust in a region where complex aerosol mixtures and semi-bright surface effects complicate satellite retrieval algorithms. TIGERZ IOP Sun photometers quantified aerosol optical depth (AOD) increases up to similar to 0.10 within and downwind of the city, with urban emissions accounting for similar to 10-20% of the IGP aerosol loading on deployment days. TIGERZ IOP area-averaged volume size distribution and single scattering albedo retrievals indicated spatially homogeneous, uniformly sized, spectrally absorbing pollution and dust particles. Aerosol absorption and size relationships were used to categorize black carbon and dust as dominant absorbers and to identify a third category in which both black carbon and dust dominate absorption. Moderate Resolution Imaging Spectroradiometer (MODIS) AOD retrievals with the lowest quality assurance (QA >= 0) flags were biased high with respect to TIGERZ IOP area-averaged measurements. MODIS AOD retrievals with QA >= 0 had moderate correlation (R-2 = 0.52-0.69) with the Kanpur AERONET site, whereas retrievals with QA > 0 were limited in number. Mesoscale-distributed Sun photometers quantified temporal and spatial variability of aerosol properties, and these results were used to validate satellite retrievals.